Pengaruh Bahasa Asing terhadap Bahasa Indonesia dan Bahasa Daerah: Peluang atau Ancaman? - I Wayan Pastika (Jurnal Kajian Bali (Journal of Bali Studies), 2012)
AbstractThe Indonesian language has developed very fast inmodernizing its vocabulary by taking in many influencesfrom foreign languages including Arabic, Dutch, English,Sanskrit, Tamil and Chinese. Similar tendencies areapparent in local languages, taking vocabulary in limitednumbers from limited sources. Balinese, for instance, hastaken loan words in classical and traditional religiousmatters from Sanskrit through Old Javanese and haslet itself be influenced almost exclusively by Englishfor modern vocabulary. Meanwhile Indonesian, whichoriginated from Malay, has developed progressively froman early history, such as Sriwijaya kingdom, to becoming acoastal linguafranca across the country and the declarationof the language as the national language. Nowadays thegovernment and educated people do very little to controlinfluence on the language. A careful academic examinationin relation to microlinguistic and macrolinguistic systems,cultural identity and nationality should be consideredseriously when new foreign words are taken as part ofthe Indonesian vocabulary. Otherwise, in the long run, thenational language will lose its identity and spoken andwritten Indonesian will be massively shaped by Englishelements. This kind of tendency has been very widespreadin recent years.